2019
DOI: 10.1177/1076029619877458
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Impact of Coagulation and Fibrinolysis Markers for Predicting Postoperative Venous Thromboembolism in Total Joint Arthroplasty Patients

Abstract: One common complication after joint arthroplasty is venous thromboembolism (VTE). Therefore, it is essential to measure the changes in coagulation and fibrinolysis in order to predict VTE among patients who underwent joint arthroplasty. This study aimed to identify potential useful biomarkers for prognosing to VTE. This was a prospective cohort study enrolling 83 patients who underwent joint arthroplasty. The levels of d-dimer, thrombin–antithrombin complex (TAT), plasmin–α2-antiplasmin complex (PIC), soluble … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 53 publications
1
10
0
Order By: Relevance
“… 27 Both t-PAIC and TM are molecules involved in the endothelial system. 28 Increased t-PAIC and TM can be used to infer endothelial cell injury, 29 which is consistent with elevated FⅧ: c and vWF: Ag, as previously mentioned. Furthermore, t-PAIC is a fibrinolytic factor, which can be used to evaluate fibrinolytic activation together with PIC.…”
Section: Discussionsupporting
confidence: 64%
“… 27 Both t-PAIC and TM are molecules involved in the endothelial system. 28 Increased t-PAIC and TM can be used to infer endothelial cell injury, 29 which is consistent with elevated FⅧ: c and vWF: Ag, as previously mentioned. Furthermore, t-PAIC is a fibrinolytic factor, which can be used to evaluate fibrinolytic activation together with PIC.…”
Section: Discussionsupporting
confidence: 64%
“…Researchers have found that FM level rises earlier than other indicators in predicting thrombotic events. [17][18][19][20][21] In this study, FM and D-dimer of 162 AIS patients who were admitted within 6 hours of onset without arteriovenous thrombolysis or mechanical thrombectomy were detected. We found that FM and D-dimers were significantly higher in AIS patients than in normal subjects.…”
Section: Discussionmentioning
confidence: 90%
“…" peak thrombin associated with twofold VTE risk 157 " F1 þ 2 and D-dimer associated with threefold VTE risk 156 " TAT without corresponding " plasmin-antiplasmin complex associated with " VTE risk 158 Liver cirrhosis-associated VTE " thrombin generation associated with presence of liver cirrhosis but not thrombosis 160 Postoperative VTE " postoperative TAT associated with " VTE risk in alloplasty 161 or fracture surgery, 162 but not superior to fibrin D-dimer 161 Thrombophilia " peak thrombin and ETP associated with " VTE risk in families with heterozygous FV Leiden 163,164 VTE in the general population " peak thrombin associated with " risk of first 165,190 or recurrent [166][167][168][169] VTE…”
Section: Cancer-associated Vtementioning
confidence: 99%